2011
DOI: 10.1371/journal.pone.0021647
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Counteracts the Anti-Inflammatory Effect of Fish Oil in Adipose Tissue and Increases Obesity Development in Mice

Abstract: BackgroundPolyunsaturated n-3 fatty acids (n-3 PUFAs) are reported to protect against high fat diet-induced obesity and inflammation in adipose tissue. Here we aimed to investigate if the amount of sucrose in the background diet influences the ability of n-3 PUFAs to protect against diet-induced obesity, adipose tissue inflammation and glucose intolerance.Methodology/Principal FindingsWe fed C57BL/6J mice a protein- (casein) or sucrose-based high fat diet supplemented with fish oil or corn oil for 9 weeks. Irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 60 publications
11
54
1
Order By: Relevance
“…Although circulating levels of inflammatory markers such as IL-6 and TNF␣ were not affected by the dietary carbohydrate source, obese mice had higher expression of macrophage markers in adipose tissue. This is in line with our earlier study where we showed that obesity rather than the n-3:n-6 PUFA ratio in both feed and adipose tissues appeared to determine the expression levels of macrophage markers in adipose tissue (40). Of note, expression of macrophage markers in the obese state was as prominent in subcutaneous iWAT as in eWAT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although circulating levels of inflammatory markers such as IL-6 and TNF␣ were not affected by the dietary carbohydrate source, obese mice had higher expression of macrophage markers in adipose tissue. This is in line with our earlier study where we showed that obesity rather than the n-3:n-6 PUFA ratio in both feed and adipose tissues appeared to determine the expression levels of macrophage markers in adipose tissue (40). Of note, expression of macrophage markers in the obese state was as prominent in subcutaneous iWAT as in eWAT.…”
Section: Discussionsupporting
confidence: 92%
“…We have described previously that sucrose counteracted the anti-inflammatory effect of fish oil in adipose tissue and increased obesity development in mice (40). Here, we show that the glucose moiety of sucrose was responsible for this effect, and this effect of sucrose can be mimicked by high-GI starch.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Dietary n-3 PUFA agonists of PPAR␣ lower glucose-induced hypertriglyceridemia and improve lipoprotein patterns in normoglycemic or well-controlled diabetic individuals (45-47, 90, 130). Paradoxically, some reports in rodents (57,106) as well as human subjects (49,72,90,111) Wild-type mouse primary hepatocytes were cultured with medium containing 40 M fatty acid-free albumin and either 6 or 20 mM glucose for 1 h as described in MATERIALS AND METHODS. Culture medium and hepatocytes were then collected and cytosolic glucose level was determined as described in MATERIALS AND METHODS.…”
Section: Discussionmentioning
confidence: 99%